Full-scale trial embankment and numerical analysis of mortar column inclusion and high-strength geotextile-reinforced load transfer platform on peat - Himawan, Agus; Sahadewa, Andhika; Irsyam, Masyhur; Mikhail, Reguel; Suhendra, Idwan; Rifai, Muchamad; Beckhaus, Karsten; Widodo, Yasin; Moormann, Christian; Schweiger, Helmut F.; Hakim, Abi Maulana; Nawir, Hasbullah; et al. (Frontiers in Built Environment, 2024)
Pile-supported embankments have been recognized as long-standing solutions for construction in compressible soft soils. Instead of improving the physical and mechanical properties of the soft soil, this method emphasizes efforts to transfer the embankment load to a competent layer below the compressible layer. Mortar column inclusion (inklusi kolom mortar or IKM) is recognized as one of the rigid inclusions in a pile-supported embankment. The IKM combined with a load transfer platform (LTP) has been widely utilized to support embankments. Studies on pile-supported embankments have generally focused on the arching mechanisms and geotextile tensile force evaluations; however, most of these investigations were conducted on soft cohesive soils. The application of pile-supported embankment on peat has rarely been studied comprehensively. This study presents a full-scale trial embankment on peat in West Sumatra, Indonesia. The 8-m-high trial embankment was supported by a series of IKM piles and a geotextile-reinforced LTP layer; instruments were then installed in the embankment, ground, LTP, geotextile, and IKM. These instruments included a series of vibrating wire earth pressure cells, vibrating wire strain gages, fiber optic sensors, vibrating wire piezometers, settlement profilers, settlement plates, and inclinometers. The instruments provided observations on the ground movements, IKM displacements, and stresses in the materials. Comprehensive evaluations from field monitoring allowed study of load transfer via the arching mechanism, deformation pattern, and IKM performance in peat. Finite element analyses (FEAs) were also conducted for comparison and verification. The field monitoring results and FEAs showed good agreement, thereby demonstrating the potential of the proposed ground improvement method for embankment construction on peat.